The evolutionary history of Drosophila buzzatii. - Hasson, E.; Fanara, J.J.; Rodriguez, C.; Vilardi, J.C.; Reig, O.A.; Fontdevila, A. (Heredity, 1992)
We demonstrate a genetic correlation between rearrangements of the second chromosome of D. buzzatii and thorax length, as a measure of body size. The results indicate that 2j and 2jz3 arrangements are correlated with large size, whereas 2st arrangement is correlated with small size. Some inversions (2st and 2jz3) show dominant effects and others (2j/jz3) exhibit overdominance. These results show that at least 25 per cent of body size variation may be accounted for by the studied karyotypes. The possible integration of the genotypic, phenotypic and fitness levels, and also the possible implications to life-history evolution theories, are discussed. These results suggest that, under moderate to high heritability values, some kinds of chromosomal endocyclic and/or balancing selection may be valuable mechanisms for maintenance of body size variation.